PENGARUH GROUP INVESTIGATION DAN GAYA BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI MAHASISWA PENDIDIKAN IPS - Amin, Saiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study aims to 1) determine the effect of the Group Investigation model on geography learning outcomes; 2) knowing the effect of learning styles on geography learning outcomes; and 3) knowing the interaction between the Group Investigation model and learning styles towards geography learning outcomes. The study design used quasi-experimental with a simple 2x3 factorial design, which refers to the pretest-posttest control group design. Analysis of learning outcome data using the Two Path Analysis of Variance ANOVA technique at a significance level of 5%. The results of the study show that 1) the Group Investigation model influences the geography learning outcomes of PIPS students at Maulana Malik Ibrahim State Islamic University of Malang; 2) learning styles influence the geography learning outcomes of PIPS students at Maulana Malik Ibrahim State Islamic University of Malang; 3) GI models and learning styles do not interact significantly influence the geography learning outcomes of PIPS students at Maulana Malik Ibrahim State Islamic University of Malang.Keywords: group investigation; learning style; geography learning outcomes